Accounting for Natural Uncertainty Within Monitoring Systems for Induced Seismicity Based on Earthquake Magnitudes - Roy, Corinna; Nowacki, Andy; Zhang, Xin; Curtis, Andrew; Baptie, Brian (Frontiers in Earth Science, 2021)
To reduce the probability of future large earthquakes, traffic light systems (TLS) define appropriate reactions to induced seismicity depending on its local earthquake magnitude (M_L). The impact of velocity uncertainties and station site effects may be greater than a whole magnitude unit of M_L: this may make the difference between a decision to continue (``green" TLS zone) and an immediate stop of operations (``red" zone). We show how to include these uncertainties in TLS thresholds such that the risk of exceeding a threshold is minimized, or that the certainty of excedance is maximized. We demonstrate that with the new TLS, a red-light threshold would have been encountered earlier in the hydraulic fracturing operation at Preston New Road, UK, potentially avoiding the later large magnitude events. It is critical to establish systems which permit regulators to account for uncertainties when managing risk.